FAKTOR–FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Devi Irianti Lestari, 14.05.52.0134; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of Gross Domestic Product, Total Population, Room Occupancy Rate, Government Expenditure and Inflation on Local Own Revenue in Regency / City in Central Java Province 2014-2016. Population in this research is all Regency and City in Central Java Province. The sample of this research are 35 regencies and cities in Central Java Province with period 2014-2016. This study uses secondary data obtained from BPS Central Java Province. The method of analysis used in this study is multiple linear regression. Based on the results of the study can be concluded that the number of residents have a significant positive effect on Local Revenue and Inflation have a significant negative effect on Local Revenue. While GRDP, Room Occupancy Rate positively insignificant effect on Local Revenue and Government Expenditure have negative effect not significant to Local Original Revenue. Keywords: GRDP, Population, Occupancy Room Rate, Government Expenditure and Inflation